Determination of amino acids in sugarcane vinasse by ion chromatographic using nickel nanoparticles on reduced graphene oxide modified electrode - da Silva, José Luiz [UNESP]; Beluomini, Maísa Azevedo [UNESP]; Sedenho, Graziela Cristina [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2017)
The present work is aimed at investigating nickel nanoparticles on reduced graphene oxide modified electrode as an amperometric detector along with anion-exchange chromatography. The modified electrode was found to exhibit electrocatalytic oxidation efficiently in relation to amino acids with high stability. The effects of hydroxide and acetate as mobile phase on the retention time, retention factor, separation factor, and peak resolution were subjected to thorough evaluation. The proposed method presented linear ranges from 2.5 × 10− 6 to 1.0 × 10− 3 mol L− 1 with excellent correlation coefficient of at least 0.9997 in optimized anion-exchange chromatographic conditions. The limits of detection for all the compounds analyzed ranged from 8.7 × 10− 7 to 2.0 × 10− 5 mol L− 1. The amperometric sensitivity was found to be within the range of 3.3 × 105 and 5.3 × 106 nA mol− 1 L. The recovery study showed that the method has good accuracy and repeatability, with recoveries between 95 ± 4.7 and 100 ± 1.7%. Experiment results obtained demonstrated that the sensor has relatively good long-term stability, accuracy, and sensitivity, besides being devoid of interference. The proposed analytical method was applied towards the determination of amino acids in sugarcane vinasse sample obtained from a sugar and ethanol plant.
Keywords: Amino acids; Amperometric detector; Electrochemical detection; Stillage; Wastewater